The microstructure effect on fatigue and dwell-fatigue in a nickel-based superalloy. (December 2022) - Peng, Zichao; Zheng, Zebang; Wang, Xuqing; Zou, Jinwen
Abstract: In this study, the fatigue behaviors of a nickel-based superalloy FGH96 with different microstructural morphologies generated from different heat-treatment processes were investigated. The fatigue and dwell-fatigue tests with the same maximum stress of 1200 MPa were conducted at 650 °C. The relationship between the γ' morphology and the fatigue properties was established. The results indicate that the critical shearing stress of dislocation movement played a key role in affecting fatigue life. No apparent difference can be observed from the fracture morphology at the macroscopic scale for normal fatigue and dwell-fatigue tests. However, in the crack initiation region, the crack was observed to grow along the grain boundary for the dwell-fatigue condition, resulting in the intergranular fracture, similar to creep failure. The introduction of dwell time in the fatigue loading brings larger cyclic strain deformation originates from massive dislocation slip. The dwell debit for the considered loading condition is about 100 times. Highlights: The size of γ′ precipitate played a key role in determining fatigue and dwell-fatigue life. When the applied stress is 1200 MPa and the dwell time is 2 min, the dwell debit is about 100 times. Dwell time brings the larger cyclic strain deformation and significant damage to the service life. The fracture morphology of dwell-fatigue combines the characters of both fatigue and creep.